Cross-Sector Collaboration in Public Service Innovation: The Implementation of the One Baby Three Documents Program in Bintan Regency - Assun Ani; Armauliza Septiawan; Okparizan Okparizan (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Public service innovation is an important strategy for improving integrated and sustainable healthcare services. This study analyses healthcare service innovation through the One Baby Three Documents Program at Kelong Public Health Centre, Bintan Regency. It used a descriptive qualitative approach, with data collected through interviews, observations, and documentation. Data were analysed using the interactive model of Miles, Huberman, and Saldaña, while Osborne and Brown’s public innovation theory served as the analytical framework, covering dynamic capability, adaptability, collaboration, learning organisation, and co-production. The findings show that the program integrates maternal and child healthcare services with civil registration services by issuing three essential documents, namely Birth Certificate, Family Card, and Child Identity Card, within one service process. Its implementation is supported by organisational adaptability, cross-sector collaboration, continuous staff capacity building, and community participation. During 2023 to 2024, the program served 109 newborns and improved early access to civil registration documents. However, limited digital infrastructure and suboptimal public participation remain key challenges. This study concludes that the program represents a sustainable healthcare service innovation through service integration and inter-agency collaboration.